Why are joint arthroplasty registers needed? Part 1. (on the example of registers of knee arthroplasty) - Zazirnyi, I. (TERRA ORTHOPAEDICA, 2023)
This article examines the creation, assignment and management of knee arthroplasty registries. Methods of collecting relevant data, cost and ways of using thinformation are considered. Registries should strive to collect and analyze data of interest to both researchers and administrators. It is important to realize that without adequate research there will be no basis for real quality improvement. Registries have now become important tools in evidence-based practice. New implants and techniques are constantly being introduced, some of which do not work as expected. Registries will continue to be important tools for identifying problems and minimizing losses for years to come. They are important to the specialty as a whole because a well-documented profession is better equipped to compete for strained medical resources. Healthcare providers are more likely to provide funding when they can show past funding results, document treatment outcomes, and predict future trends.